Sensibility of Children of Different Age Groups to Alarm Intervention for Enuresis - Kosilov, KV; Loparev, SA; Ivanovskaya, MA; Kosilova, LV (Journal of Nepal Paediatric Society, 2015)
Introduction: Prevalence of primary monosymptomatic night enuresis (PMNE) is high. Age, gender and race of patients, as well as diagnostics criteria used by the researchers, have an impact on the data on enuresis prevalence, and alarm intervention has been used for enuresis treatment for several decades The purpose of this study is to try to find out the difference in efficiency of the Alarm intervention for children of different age for improving recommendations on usage of alarm systems. Materials and Methods: Sampling consisted of 399 persons: 238 males and 161 females suffering PMNE. A method of random numbers was used for group randomization. Persons of both genders at the age of 7 to 15 years old having at least two episodes of nocturnal enuresis per week were included into the treatment group. Then they were distributed into three subgroups where questionnaires were filled, uro-flowmetry and investigations were done Treatment control was carried out with the help of bladder diaries where episodes of nocturnal, spontaneous awakenings in case of desire to urinate and dry nights were registered. Alarm intervention was conducted by standard method with the use of device Wet Stop/ BYE-WET by PALCO LABS, Inc (USA). Results: Initial data showed that children of junior and average age subgroups show optimal response to conducted therapy. However, the results of 10-12-yearold children proved to be stable, the result of 7-9-year-old children was significantly worse in two months after the end of treatment. Conclusion: Alarm intervention has the best direct and long-term effect on 10-12-year old children. J Nepal Paediatr Soc 2015;35(1):49-56